STUDI DISKRIPTIF KASUS FAKTOR UNDERPRICING: LABA, REPUTASI AUDITOR, KARAKTERISTIK DEWAN DAN GENDER TIGA BANK DI INDONESIA - Filipus Argentano Guntur Suryaputra (Riset Manajemen dan Akuntansi, 2021)
One of the important goals of the company is to offer shares to the public with an initial public offering (IPO) to the general public to develop its business activities. There are 3 banks that are analyzed by Ganesha Bank, Net Sharia Bank and Islamic BTPN Bank. The character of the Women's Council, Return on Equity and Underpricing is the focus in this case.